Fluorescence based HTS-compatible ligand binding assays for dopamine D3 receptors in baculovirus preparations and live cells - Tahk, Maris-Johanna; Laasfeld, Tõnis; Meriste, Elo; Brea, Jose; Loza, Maria Isabel; Majellaro, Maria; Contino, Marialessandra; Sotelo, Eddy; Rinken, Ago (Frontiers in Molecular Biosciences, 2023)
Dopamine receptors are G-protein-coupled receptors that are connected to severe neurological disorders. The development of new ligands targeting these receptors enables gaining a deeper insight into the receptor functioning, including binding mechanisms, kinetics and oligomerization. Novel fluorescent probes allow the development of more efficient, cheaper, reliable and scalable high-throughput screening systems, which speeds up the drug development process. In this study, we used a novel Cy3B labelled commercially available fluorescent ligand CELT-419 for developing dopamine D3 receptor-ligand binding assays with fluorescence polarization and quantitative live cell epifluorescence microscopy. The fluorescence anisotropy assay using 384-well plates achieved Z’ value of 0.71, which is suitable for high-throughput screening of ligand binding. The assay can also be used to determine the kinetics of both the fluorescent ligand as well as some reference unlabeled ligands. Furthermore, CELT-419 was also used with live HEK293-D3R cells in epifluorescence microscopy imaging for deep-learning-based ligand binding quantification. This makes CELT-419 quite a universal fluorescence probe which has the potential to be also used in more advanced microscopy techniques resulting in more comparable studies.